2021
DOI: 10.1136/rmdopen-2021-002019
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, safety and reactogenicity of a heterogeneous booster following the CoronaVac inactivated SARS-CoV-2 vaccine in patients with SLE: a case series

Abstract: Since the COVID-19 pandemic, CoronaVac, an inactivated SARS-CoV-2 vaccine, has been widely deployed in several countries for emergency use. However, the immunogenicity of the inactivated vaccine was relatively lower when compared to other vaccine types and was even more attenuated in autoimmune patients with rheumatic disease. A third-dose SARS-CoV-2 vaccination in immunosuppressed population is recommended in order to improve immune response. However, the data were limited to those initially received mRNA or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…The screening process is illustrated in the PRISMA flowchart in Figure 1 . Of these studies, there were 12 observational studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], one randomised-controlled trial [ 33 ], and four case series [ 34 , 35 , 36 , 37 ]. The key trial characteristics of each included study are reported in Table 1 , with a comparison of the characteristics of the studies included in the meta-analysis in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The screening process is illustrated in the PRISMA flowchart in Figure 1 . Of these studies, there were 12 observational studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], one randomised-controlled trial [ 33 ], and four case series [ 34 , 35 , 36 , 37 ]. The key trial characteristics of each included study are reported in Table 1 , with a comparison of the characteristics of the studies included in the meta-analysis in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 booster vaccines administered in the studies included mRNA (Pfizer-BioNTech, BNT162b2 and Moderna, mRNA-1273) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 34 , 35 , 36 , 37 ], non-replicating viral vector (AstraZeneca, AZD1222 and Janssen, Ad26.COV2.S) [ 21 , 28 , 29 , 30 , 34 , 35 , 36 , 37 ], protein subunit (Novavax, NVX-CoV2373) [ 33 ] and inactivated (Sinovac, CoronaVac) vaccines [ 35 ]. Bonelli et al involved two cohorts receiving mRNA vaccines as the primary series, but one received heterologous AstraZeneca booster doses while the other received homologous mRNA boosters [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Примечательно сообщение исследователей из Таиланда, которые установили, что третья бустерная доза мРНК-или вирусной векторной вакцины, назначенная после инактивированной вакцины (CoronaVac), хорошо переносится и вызывает значительный гуморальный и клеточный иммунный ответ у неактивных пациентов с СКВ, получающих поддерживающую иммуносупрессивную терапию. В течение периода исследования обострения СКВ не было ни у одного из пациентов [49].…”
Section: риск поствакцинальных ня не связанных с основным иврзunclassified